Ligand-Enabled meta-C–H Activation Using a Transient Mediator - Wang, Xiao-Chen (Nature, 2015)
Achieving site selectivity in C–H functionalization reactions is a significant challenge, especially when the target C–H bond is distant from existing functional groups.(1–5) Coordination of a functional group to a metal catalyst is often a key driving force and control element in many important reactions including asymmetric hydrogenation,(6) epoxidation(7, 8), and lithiation(9). Exploitation of this effect has led to the development of a broad range of directed C–H activation reactions.(10–14) However, such C–H activation methods are limited to proximal C–H bonds, which are spatially and geometrically accessible from the directing functional group. Development of meta-selective C–H functionalizations remains a significant challenge.(1–5,15–17) We recently developed a U- shaped template that can be used to overcome this constraint and have shown that it can be used to selectively activate remote meta-C–H bonds.(1, 2) While this approach has proven applicable for a diverse set of substrates and catalytic transformations,(3–5) the need for a covalently attached complex template is a significant drawback for synthetic applications. In this manuscript, we report an alternative approach, one that employs norbornene as a transient mediator to achieve meta-selective C–H activation with a simple and common ortho-directing group. The use of a newly developed pyridine-based ligand is crucial for relaying the palladium catalyst to the meta position by norbornene following initial ortho- C–H activation. Thus, this catalytic reaction demonstrates the feasibility of switching ortho-selectivity to meta-selectivity in C–H activation of the same substrate by catalyst control.